Epidemiology, species distribution and outcome of nosocomial Candida spp.bloodstream infection in Shanghai - Zhitao Yang; Lin Wu; Xiaoying Liu; Min Zhou; Jie Li; Jiayin Wu; Yong Cai; Enqiang Mao; Erzhen Chen; Olivier Lortholary (2014)
Abstract Background Yeasts, mostly Candida , are important causes of bloodstream infections (BSI), responsible for significant mortality and morbidity among hospitalized patients. The epidemiology and species distribution vary from different regions. The goals of this study were to report the current epidemiology of Candida BSI in a Shanghai Teaching Hospital and estimate the impact of appropriate antifungal therapy on the outcome. Methods From January 2008 to December 2012, all consecutive patients who developed Candida BSI at Ruijin University Hospital were enrolled. Underlying diseases, clinical severity, species distribution, antifungal therapy and its impact on the outcome were analyzed. Results A total of 121 episodes of Candida BSI were identified, with an incidence of 0.32 episodes/1,000 admissions (0.21 in 2008 and 0.42 in 2012) The proportion of candidemia caused by non- albicans species (62.8%), including C. parapsilosis (19.8%), C. tropicalis (14.9%), C. glabrata (7.4%), C. guilliermondii (5.8%), C. sake (5.0%) was higher than that of candidemia caused by C. albicans (37.2%). The overall crude 28-day mortality was 28.1% and significantly reduced with appropriate empiric antifungal therapy administered within 5 days (P = 0.006). Advanced age (OR 1.04; P = 0.014), neutropenia < 500/mm 3 (OR 17.44; P < 0.001) were independent risk factors for 28-day mortality, while appropriate empiric antifungal therapy (OR 0.369; P = 0.035) was protective against 28-day mortality. Conclusion The epidemiology of candidemia in Shanghai differed from that observed in Western countries. Appropriate empiric antifungal therapy influenced the short-term survival.